2008
DOI: 10.1371/journal.pone.0002620
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Practices Regarding Dengue Fever among the Adult Population of Dengue Hit Cosmopolitan

Abstract: BackgroundThe World health Organization (WHO) declares dengue and dengue hemorrhagic fever to be endemic in South Asia. Despite the magnitude of problem, no documented evidence exists in Pakistan which reveals the awareness and practices of the country's adult population regarding dengue fever, its spread, symptoms, treatment and prevention. This study was conducted to assess the level of knowledge, attitudes and practices regarding dengue fever in people visiting tertiary care hospitals in Karachi, Pakistan.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
98
9
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(157 citation statements)
references
References 16 publications
42
98
9
3
Order By: Relevance
“…In a In a similar hospital based study done by Itrat et al, about 47.5% respondents stated the use of mosquito coils/ mat as a preventive measure against mosquito. 16 In our study, about 66% of the respondents spend less than 100 Rupees a month for vector control measures. In a similar study done by Boratne et al in Puducherry in 2010, it was found out that about 62% of respondents spend less than 100 Rupees a month for vector control measures.…”
Section: Discussionmentioning
confidence: 67%
“…In a In a similar hospital based study done by Itrat et al, about 47.5% respondents stated the use of mosquito coils/ mat as a preventive measure against mosquito. 16 In our study, about 66% of the respondents spend less than 100 Rupees a month for vector control measures. In a similar study done by Boratne et al in Puducherry in 2010, it was found out that about 62% of respondents spend less than 100 Rupees a month for vector control measures.…”
Section: Discussionmentioning
confidence: 67%
“…Use of antimosquito spray was the most prevalent (48.1%) preventive measure. 15 Itrat et al found that one-half (51.1%) of those interrogated were knowing that the dengue mosquito breeds in clean standing water. 16 It was similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Our study also suggests that respondents with tertiary education level had a significantly higher knowledge and attitude score. Previous research has shown that the level of education has a significant impact on knowledge [27,36] and attitude [24,37] related to mosquito-borne disease like dengue. Thus, more effective education programs for population awareness need to be implemented among people with low education level especially in areas where the mosquitoborne diseases dominate.…”
Section: Discussionmentioning
confidence: 99%